#TITLE_ALTERNATIVE# - MOHAMMAD FAIZAL PRATOMO (NIM : 10209052),
Generally, geothermal systems consists of an impermeable heat source (hot rock), permeable reservoir rock and hydrothermal flow. However, some of the geothermal systems have a cap rock which is impermeable. Heat transfer occurred due to hydrothermal flow. Heat transfer occurs in the geothermal system are convection and conduction. In exploration and exploitation of geothermal systems, information about fluid flow and temperature is needed. This information is used to determine the location of production wells and recharge and discharge areas. Fluid flow modeling is done by utilizing the Brinkman equations , Darcy law and the equation of thermal equilibrium or Conduction Convection equation. Brinkman equations is used to determine the value of the velocity of fluid flow . Darcy law applies when the fluid flow is very slow. By using Darcy Law, the value of the velocity of the fluid flow can be seen which will be compared with result using the Brinkman equation. Distribution of temperature is described by the equation of thermal equilibrium. The result of this present study will be fluid flow and distribution of temperature modeling in Unzen. Modeling was done by using COMSOL Multiphysics software.